Fitness and microbial networks of the common wasp, Vespula vulgaris (Hymenoptera: Vespidae), in its native and introduced ranges. (9th March 2019) - Gruber, Monica A. M.; Quinn, Oliver; Baty, James W.; Dobelmann, Jana; Haywood, John; Wenseleers, Tom; Lester, Philip J.
Abstract : 1. Variation in microbial communities between populations is increasingly hypothesised to affect animal fitness and performance, including for invasive species. Pathogenic species may be lost during the introduction process, enhancing invader fitness and abundance. 2. This study assessed fitness, immune gene expression, and microbial network complexity of invasive common wasps, Vespula vulgaris . Microbial networks were assayed using 16S and 18S sequencing and gene expression arrays in the native (Belgium) and introduced range (New Zealand). The immune gene expression of the wasp Down syndrome cell adhesion molecule ( Dscam ) gene homologue was examined. Dscam expression can be induced by viruses, Gram‐positive and Gram‐negative bacteria, and parasites. 3. Individual nest fitness was higher in the native range of Belgium than in the introduced New Zealand range. Microbial communities of wasps in the introduced range were more diverse with more complex networks, although some microorganisms were range‐specific. Microbial networks in the introduced range showed higher clustering coefficients, number of connected paths, network centralisation, number of neighbours and network density. 4. Larvae, workers, virgin and foundress queens had higher expression of Dscam in the New Zealand samples. These immune gene expression patterns were associated with higher pathogen pressure and lower relative fitness. 5. Epidemiological theory predicts that a high density of pathogen and microbial hosts should result in a high rate of disease infection, prevalence, and highly connected microbial networks. The results of this study support these predictions. Wasps displayed lower relative fitness and more highly connected microbial networks in New Zealand than in Belgium. Abstract : This study assessed fitness, immune gene expression, and microbial network complexity of invasive common wasps, Vespula vulgaris . Contrary to theoretical expectations, estimates of fitness were higher in the native range. Microbial communities of wasps in the introduced range were more diverse with more complex networks. A comparatively higher expression of an immune gene in the invaded range was observed. Epidemiological theory predicts that high densities of pathogens and hosts will result in high rates of disease infection, prevalence, and highly connected microbial networks. The results of this study support these predictions.